TESS shines light on the origin of the ambiguous nuclear transient ASASSN-18el. Issue 3 (16th March 2023) - Hinkle, Jason T; Kochanek, Christopher S; Shappee, Benjamin J; Vallely, Patrick J; Auchettl, Katie; Fausnaugh, Michael; Holoien, Thomas W-S; Treiber, Helena P; Payne, Anna V; Gaudi, B Scott; Stassun, Keivan G; Thompson, Todd A; et al.
ABSTRACT: We analyse high-cadence data from the Transiting Exoplanet Survey Satellite ( TESS ) of the ambiguous nuclear transient (ANT) ASASSN-18el. The optical changing-look phenomenon in ASASSN-18el has been argued to be due to either a drastic change in the accretion rate of the existing active galactic nucleus (AGN) or the result of a tidal disruption event (TDE). Throughout the TESS observations, short-time-scale stochastic variability is seen, consistent with an AGN. We are able to fit the TESS light curve with a damped-random-walk (DRW) model and recover a rest-frame variability amplitude of $\hat{σ } = 0.93 ± 0.02$ mJy and a rest-frame time-scale of $τ _{DRW} = 20^{+15}_{-6}$ d. We find that the estimated τ DRW for ASASSN-18el is broadly consistent with an apparent relationship between the DRW time-scale and central supermassive black hole mass. The large-amplitude stochastic variability of ASASSN-18el, particularly during late stages of the flare, suggests that the origin of this ANT is likely due to extreme AGN activity rather than a TDE.